2020
DOI: 10.1186/s12881-020-01063-5
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics and prenatal diagnosis for 22 families in Henan Province of China with X-linked agammaglobulinemia (XLA) related to Bruton’s tyrosine kinase (BTK) gene mutations

Abstract: Background: X-linked agammaglobulinaemia (XLA) is a rare immunodeficiency disease for which recurrent severe infection is the major clinical symptom. BTK is the main causative gene, with X chromosome recessive inheritance. However, the mutations reported to date do not fully explain the disorder. Methods: We detected the percentage of CD19+ B cells and serum immunoglobulin (IgG, IgA, and IgM) levels by flow cytometry and rate scatter immunoturbidimetry, and investigated the BTK mutation profile in 22 XLA patie… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Genomic DNA was extracted from the aborted fetus and peripheral leukocytes from the mothers and the grandma of the patients, according to standard protocols (Gao et al, 2020 ). Whole‐exon sequencing was used to analyze the gene variation and screen the candidate gene, followed by PCR and Sanger sequencing to confirm the L1CAM gene.…”
Section: Case Reportmentioning
confidence: 99%
“…Genomic DNA was extracted from the aborted fetus and peripheral leukocytes from the mothers and the grandma of the patients, according to standard protocols (Gao et al, 2020 ). Whole‐exon sequencing was used to analyze the gene variation and screen the candidate gene, followed by PCR and Sanger sequencing to confirm the L1CAM gene.…”
Section: Case Reportmentioning
confidence: 99%
“…These methods analyse fetal DNA to identify genetic mutations associated with IEI. Several studies have reported successful cases of prenatal diagnoses using these approaches, such as CGD, 32 44 45 WAS, 46 SCID, 35 XLA 47 and XLP. 48 Nevertheless, certain invasive techniques carry risks of miscarriage.…”
Section: Introductionmentioning
confidence: 99%
“…Both children and their families may feel isolated and stigmatized in education, employment and the workplace, or lack social support or understanding [9,10]. Different studies have analyzed the quality of life in primary immunodeficiencies such as severe combined immunodeficiency due to RAG1 and RAG2 deficiency [10], common variable immunodeficiency [11] or X-linked immunodeficiency (Bruton's agammaglobulinemia) [12]. Among the immunodeficiencies by default in phagocytosis is chronic granulomatous disease (CGD).…”
Section: Introductionmentioning
confidence: 99%